Analisis Efektivitas OPAC dalam Mendukung Mahasiswa Mencari Referensi Skripsi Menggunakan Model Delone & Mclean - Andriani, Annisa; Faradillah; Kholik, Abdul (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
Online Public Access Catalog (OPAC) is a service provided by the UIGM Library to support the academic needs of students, particularly in accessing thesis collections. Although this system has supported access to academic information, there are still limitations, particularly in the presentation of data that is not yet detailed. This requires users to come directly to the library to obtain comprehensive information. This condition poses a unique challenge for working-class students, given the time constraints they face due to work schedules that do not align with library service hours. This research aims to analyze the effectiveness of OPAC in supporting students in finding thesis references and to identify the factors that influence its effectiveness based on the Delone and McLean model. The research results show that out of the nine hypotheses tested, six were accepted and three were rejected. These findings indicate that information quality, system quality, usage, and user satisfaction significantly contribute to the effectiveness of OPAC in thesis reference searches. Nevertheless, the effectiveness of OPAC still has room for further development.